Effectiveness of Cooperative Learning Picture to Picture Plant Organ Material for High School Students - Rizkiyah, Nur (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Practical learning still focuses on theory alone. Biology learning requires continuous cooperation and practice. The aim of this research is to determine the effectiveness of cooperative learning picture to picture on learning outcomes in Biolagi, plant organ material in class XI high school students. This research method is an experimental method with one group pretest and posttest. The respondents who took part in this research were 31 class XI high school students located in Bogor Regency. Data collection was carried out by documentation and pretest and posttest. Process the data using SPSS version 26 with data normality and homogeneity tests. The test continues with the T paired sample test. The research results show that cooperative learning methods can improve student learning outcomes.